The Principal's Strategy Based on the Noble Values of the Huma Betang Philosophy in Improving Teacher Performance at Palangka 2 Public Elementary School - Carolina Fransiska; Melinda Prawati; Widya Permata Dilla; Simpun Simpun; Femmy Femmy; Kristiani Natalia; Laila Rahmawati; Maneka Ciciana; Noorlaila Noorlaila; Bambang Eko Irawan (Jurnal Pendidikan Edutama, 2026)
The purpose of this research is to determine " The Principal's Strategy Based on the Noble Values of the Huma Betang Philosophy in Improving Teacher Performance at Palangka 2 Public Elementary School ". The research method used is descriptive with a qualitative approach. Data collection techniques include observation, interviews, and documentation studies. The research subjects were the principal, vice principal, teachers, and supervisors. The results show: 1) The principal's strategy in improving teacher abilities is based on the Huma Betang philosophy through developing teacher abilities in the learning process, 2) The principal's strategy in improving teacher discipline is: a) Enforcing teacher discipline, b) Increasing teacher behavior standards, c) Implementing all regulations, 3) The principal's strategy in improving teacher motivation is to create a harmonious situation, provide all necessary equipment and provide rewards and punishments, 4) The principal's strategy in increasing teacher commitment is: holding training, bringing tutors to the school and providing opportunities for continuing education, placing teachers according to their fields, and holding meetings at the beginning of each semester.